Correlação de nutrientes e calibração da adubação boratada em pomares de oliveira (olea europaea l.) da Cultivar Arbequina no Sul do Brasil - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The cultivation area with olive trees (Olea europaea L.) has been increasing in Brazil, where the state of Rio Grande do Sul has stood out in olive oil quality and yield. However, the management practices for the crop require adjustments for local soil and climate conditions, especially the boron (B) nutrient, which affects fruit production. Aiming to improve the fertilizer recommendation system, focusing on B, studies were conducted in orchards in central region of Rio Grande do Sul, in the municipalities of Cachoeira do Sul, Caçapava do Sul, and São Gabriel, between the years 2018 and 2021. First, eight orchards were evaluated to verify the nutritional status, through chemical analyses of soil, leaf, and fruit (when fruit set was present) tissues from ten plants from each orchard. It was found that excess of nitrogen in leaf may have limited the yield and, in several orchards, there were high levels of Al3+ associated with the acidity condition in the deepest layer (20-40cm). We also observed a decrease of B content in fruits under high pH conditions in the soil, suggesting that the critical level of the element in the soil may be pH-dependent. In the second study, four orchards, ranging from 5 to 17 year-age, were evaluated by applying four B rates as ulexite (0, 25, 50, and 100 g ulexite tree-1) associated with the presence or absence of foliar fertilization. Soil and leaf samples were collected previously to the fertilizer applications and were chemically analyzed to verify the initial nutritional status (winter 2019). In the summer of 2020, fruits and leaf tissue were sampled for nutrient analysis (N, P, K, and B) and quantification of yield for further statistical analysis, and in summer of 2021, yield quantification was performed for residual effect evaluation. In 2020, when there was low fruit set due to alternate bearing, no significant differences were observed for both soil and foliar treatments. Nevertheless, in 2021, the application of 100 g ulexite tree-1 without foliar fertilization promoted the best residual effect, given by the highest yield per tree. The results in general reinforce the need to pay attention to the high B demand for olive trees, especially in orchards where soil pH was raised to high values by liming (pH > 7.0).
Keywords: Oliveira; Nutrição; Fertilização; Boro; Olive tree; Nutrition; Fertilization; Boron; CNPQ::CIENCIAS BIOLOGICAS